ANALISIS STRATEGI PEMBELAJARAN IPA DALAM BUKU TEMATIK KURIKULUM 2013 KELAS IV SD - Alma Pratiwi Husain (LPPM STAI DARUSSALAM LAMPUNG, 2019)
This article aims to find out the relevant strategies for use in science lessons, thematic books K-13 class IV theme 2 in MI / SD. The research method used is the library research approach. Data collection is carried out by examining various journals, books and documents both printed and electronic which are relevant to research studies. The results showed that the relevant learning strategies used were experiential learning strategies with experimental methods and field observations. This strategy provides a real picture because students are in direct contact with objects and nature during the learning process. The benefits of this study provide information related to relevant learning strategies for science lessons, thematic books K-13 class IV theme 2 in MI / SD.